Application of Polyimide‐based Microfluidic Devices on Acid‐catalyzed Hydrolysis of Dimethoxypropane. Issue 5 (18th February 2021) - Bobers, Jens; Forys, Elisabeth; Oldach, Bastian; Kockmann, Norbert
Abstract: Microfluidic devices intensify transport phenomena and can improve chemical processes. New manufacturing processes and materials are perpetually developed due to constantly growing interest in process intensification. In this contribution, the authors present the design and application of polyimide‐foil‐based microfluidic mixing devices manufactured by reactive ion etching. As appropriate model reaction system, acid‐catalyzed 2, 2‐dimethoxypropane (DMP) hydrolysis was chosen and investigated in three different mixing structure with varying flow rate. Energy dissipation rates were calculated to estimate mixing performances. The results show good mixing quality for Reynolds numbers between 10 and 100 and similar mixing times scales for all investigated microstructured mixers. Abstract : A mixing‐sensitive reaction system consisting of acid‐catalyzed hydrolysis of 2, 2‐dimethoxypropane and a neutralization reaction was performed in three polyimide‐based micromixing structures. Evaluating mixing quality, a power law regression of the acetone yield over the specific energy dissipation rate revealed similar mixing time scale for all microstructures.